Popularising Micro-irrigation in Pulses for higher yield and water productivity - Praharaj, C S; Singh, Ummed; Singh, N P; Shivay, Y S (Indian Farming, 2018)
With the given technology framework, substantial productivity enhancement through the existing varieties of pulses could be possible with short duration varieties that fit well in different (inter-) cropping systems so as to augment vertical expansion of pulses in the country. Mungbean for example - through development of new plant types, photo-thermo- insensitive cultivars and matching agrotechs - could help in expanding the areas of pulses further (in the non-traditional areas of the country), thereby both up- and out-scaling productivity (over seasons and locations) and overall production scenario in the country.